2020
DOI: 10.1177/0011000020915451
|View full text |Cite
|
Sign up to set email alerts
|

Counselors’ Attitudes Towards Working With Clients With Substance Use Disorders

Abstract: Substance use disorders (SUDs) are a significant and growing problem in all walks of life in Canada and the United States. Counselors are increasingly likely to have clients with SUDs regardless of their area of expertise. There is limited research on counselors’ attitudes towards working with such clients, or the factors that contribute to these attitudes. In an online survey of 263 Canadian counselors, we found attitudes were mostly positive, although statistically significantly less positive than toward wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It is shown that the quality of the application developed follows the needs of students. Besides that, the features possessed by EdukasiKarir Application make it easier for students to understand their potential well [31]. Career guidance focuses on life planning by considering one's potency [32].…”
Section: Usabilitymentioning
confidence: 99%
“…It is shown that the quality of the application developed follows the needs of students. Besides that, the features possessed by EdukasiKarir Application make it easier for students to understand their potential well [31]. Career guidance focuses on life planning by considering one's potency [32].…”
Section: Usabilitymentioning
confidence: 99%